ÁREA ELEMENTAR REPRESENTATIVA DA DENSIDADE DO SOLO DE AMOSTRAS COLETADAS EM ANÉIS VOLUMÉTRICOS VIA ANÁLISE TOMOGRÁFICA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
The computed tomography (CT) represents a technique that provides images of samples, allowing the study of different soil physical phenomena by qualitative and quantitative analysis in 2D and 3D. In the area of applied physics to porous media is a matter of investigation the definition of representative elementary areas (REA) regarding measurements of physical properties of this media. REA is related to the minimum area of a sample needed to represent its characteristics of interest. The aim of this study was to define REAs to be adopted for density (ρs) measurements from sample soil collected in volumetric rings. Having this purpose in mind, three soils with different textures were analyzed: Geric Ferralsol (GF), Rhodic Ferralsol (RF) and Eutric Nitosol (EN). Six samples from each soil were submitted to the method of volumetric ring (VR) and CT for ρs evaluation. A first generation tomograph equipped with 241Am gamma-ray source was used in the image acquisition. Consecutive areas were selected according to three different schemes (consecutive areas increasing from a first area selected at the center of the image and consecutive areas increasing from a first area selected at the inferior and superior borders of the sample) with size areas ranging from 1.2 to 678.8 mm². For ρs measurements, the following criteria were adopted: 1) relative deviation (RD) between ρs – RV and each of the areas not superior to 10, 8, 6, 4 and 2%; 2) RD between ρs - CT obtained for the last area selected inside the tomographic image and each of the remaining areas equally not superior than the criteria from item 1; 3) that at least three consecutive areas must not differ in RD values among themselves, using the variation criterion presented in items 1 and 2. It was considered that the REA for ρs was reached at the variation criteria of 4%. The REA found for ρs, according to the area selection starting from the center, superior and inferior borders of the tomographic images, were: 432.0; 393.3 and 334.0 mm² (GF), 473.1; 457.4 and 393.3 mm² (RF) and 349.7; 457.4 and 334,0 mm² (EN), respectively. The results obtained by the area selection starting from the center were assumed to be the real values of REA for the studied soils. In this study, it was also proposed an alternative criterion of analysis based on the results obtained, which use as reference, simultaneously, the methods of VR and CT. Therefore, it was possible to define that áreas measuring 432.0 mm² e 349.7 mm² provide, respectively , reliable density values for the LVA and NV soils.
Keywords: estrutura do solo; densidade do solo; análise de imagens; atenuação de raios gama; medidas elementares representativas; soil structure; image analysis; gamma ray attenuation; representative elementary measurements; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA